2014
DOI: 10.4103/0019-5413.128763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thoracic arthrodesis in prepubertal New Zealand white rabbits on cardio-pulmonary function

Abstract: Background:This experimental study was aimed at evaluating the type of cardiac and pulmonary involvement, in relation to changes of the thoracic spine and cage in prepubertal rabbits with nondeformed spine following dorsal arthrodesis. The hypothesis was that T1-T12 arthrodesis modified thoracic dimensions, but would not modify cardiopulmonary function once skeletal maturity was reached.Materials and Methods:The study was conducted in 16 female New Zealand White (NZW) rabbits. Nine rabbits were subjected to T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Rabbits were operated according to a modified “Wisconsin” technique or extra-canal dorsal T1–T12 vertebral arthrodesis, corresponding to posterior vertebral arthrodesis in bipeds, as punctually indicated in previous our works. 13 14 15 Multiple fragments of demineralized bone matrix (Grafton DBM, Osteotech Inc., Eatontown, NJ, USA) were applied, during the surgery, on each side of the spinous processes of the thoracic spine to favor fusion.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbits were operated according to a modified “Wisconsin” technique or extra-canal dorsal T1–T12 vertebral arthrodesis, corresponding to posterior vertebral arthrodesis in bipeds, as punctually indicated in previous our works. 13 14 15 Multiple fragments of demineralized bone matrix (Grafton DBM, Osteotech Inc., Eatontown, NJ, USA) were applied, during the surgery, on each side of the spinous processes of the thoracic spine to favor fusion.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…In the past, experimental studies in quadrupedal mammals showed that, when subjected to dorsal vertebral arthrodesis, such animals rarely develop scoliosis, while possible natural kyphosis is reduced. 11 12 It has then been shown experimentally in New Zealand white (NZW) rabbits that early partial or total dorso-thoracic vertebral arthrodesis affects the development of the rib cage and thoracic spine, it involves and alters vertebral values and ratios between thoracic diameters, 13 14 while it leaves the echocardiographic values unaltered and does not reveal significant disparity in the arterial blood gases of rabbits submitted to arthrodesis and sham operated rabbits; 15 other observations in dogs have reported thinning and disorganization of the growth plate. 16 17 …”
Section: Introductionmentioning
confidence: 99%